Analisis Kecepatan Krisis Dan Kecepatan Rata Rata Lumpur Pemboran Pada Pengangkatan Serbuk Bor - Cerriansyah Ramadhan; Andi Jumardi; Eltimeyansi Chrisye Randanan; Karmila; Joko Wiyono; Ipan Sampe; Darmiyati, Iin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2022)
As we know mud drilling provides many benefits in drilling operations. This needs to be considered also how the speed of the drilling mud is so in bringing drill powder above the surface so that there are no problems at will. The problem that occurs when the drill powder is not carried to the surface is the deposition at the bottom of the borehole. To see if the drilling sludge can circulate properly, it is necessary to calculate critical speed and average speed. Research data such as borehole diameter, mud weight, yield point, and plastic viscosity as well as data on each circuit component and annulus will be needed to determine flow patterns in circuits and annulus. Determination of flow patterns is also needed so that it can find out if the drilling sludge is functioning properly in the borehole. After doing calculations on the circuit then the vcDP result = 5.99 fps < V dp = 13.18 fps, VcMWD Tools = 6.28 < V MWD Tools = 26.82 fps, Vc3xDC = 6.62 fps < V 3xDC = 47.69 fps, Vc4xHWDP = 6.28 fps < V 4xHWDP = 26.82 fps, Vcjar = 6.28 fps < V jar = 26.82 fps, Vc16xHWDP = 6.76 fps < V 16xHWDP = 26.82 fps, then it is certain that the flow of mud in the circuit is turbulent so as to cause a cleaning effect on a fairly good circuit. In annulus obtained results VcaDP = 5.43 fps > V adp = 5.10 fps, VcaMWD Tools = 6.66 fps < Va MWD Tools = 10.38 fps, Vca3xDC = 6.10 fps < Va 3xDC = 8.05 fps, Vca 4xHWDP = 5.43 fps > Va 4xHWDP = 5.11 fps, Vcajar = 6.10 fps < Va jar = 8.05 fps, Vca16xHWDP = 5.43 fps > Va 16xHWDP = 5.11 fps, Looking at the results of calculations on annulus more average speed values then it can be ascertained that the flow of mud in annulus is turbulent.